Argumentation and rational change of opinion - Szymanek, Krzysztof (Folia Philosophica, 2010)
Report from the conference “Argumentation and Rational Change of Beliefs,” which took place from April 1 to 3, 2009, in Ustroń. The conference was organized by the Institute of Philosophy of the Faculty of Social Sciences at the University of Silesia in Katowice.